Autoimmune disease and sickle cell anaemia: 'Intersecting pathways and differential diagnosis'. (4th March 2022) - Piccin, Andrea; O'Connor‐Byrne, Niamh; Daves, Massimo; Lynch, Kelvin; Farshbaf, Amin Daei; Martin‐Loeches, Ignacio
Abstract: Sickle cell disease (SCD) is an inherited disorder, which occurs due to a single gene mutation. It has multisystemic manifestations, affecting millions of people worldwide. The effect of SCD on joints and musculature can overlap with clinical features of autoimmune disease (AD). It is therefore difficult for clinical haematologists and physicians treating SCD patients to discriminate between these two conditions clinically. A delay in diagnosis leads to untreated symptoms and treatment differs considerably. An accurate knowledge of clinical findings and laboratory results of AD and SCD can help physicians avoid this. In the review that follows, we examine the existing literature on SCD and AD, and describe the features that may distinguish SCD and autoimmune disease such as systemic lupus erythematosus and rheumatoid arthritis. We aim to guide clinical haematologists and physicians towards a more rapid diagnosis of AD in sickle cell anaemia patients, by correct interpretation of the clinical assessment and commonly available diagnostics.